3D Graphene Scaffolds for Skeletal Muscle Regeneration: Future Perspectives - Palmieri, Valentina; Sciandra, Francesca; Bozzi, Manuela; De Spirito, Marco; Papi, Massimiliano (Frontiers in Bioengineering and Biotechnology, 2020)
Although skeletal muscle can regenerate after injury, in chronic damages or in traumatic injuries its endogenous self-regeneration is impaired. Consequently, tissue engineering approaches are promising tools for improving skeletal muscle cells proliferation and engraftment. In the last decade, graphene and its derivates are being explored as novel biomaterials for scaffolds production for skeletal muscle repair. This review describes 3D graphene-based materials that are currently used to generate complex structures able not only to guide cell alignment and fusion but also to stimulate muscle contraction thanks to their electrical conductivity. Graphene is an allotrope of carbon that has indeed unique mechanical, electrical and surface properties and has been functionalized to interact with a wide range of synthetic and natural polymers resembling native musculoskeletal tissue. More importantly, graphene can stimulate stem cell differentiation and has been studied for cardiac, neuronal, bone, skin, adipose, and cartilage tissue regeneration. Here we recapitulate recent findings on 3D scaffolds for skeletal muscle repairing and give some hints for future research in multifunctional graphene implants.